Formas de referenciação a pessoas: uma abordagem variacionista - Maria Alice Mota (2013)
This work aims to study the use of the referral forms to people in Oral Brazilian Portuguese, starting from hypothesis that the choices made by the speakers are conditioned by social and linguistic factors. The corpus was formed by a sample consisting of 24 interviews with residents in two distinct geographical areas and with diverse population index and human development: the Aparecida do Mundo Novo municipality (MG) and Belo Horizonte city (MG), a chosen region so that they could make a comparative study with the studied community, since, as we have known, the Minas Gerais state has different dialect areas, and Belo Horizonte is a metropolitan center that welcomes people from different regions. For the analysis, two variants were identified: (1) the civil name as José, José Paulo, José dos Santos, and (2) other anthroponyms different civil names such as Zé, Zé de Paulo, Zé de Juca. It was selected the instances in which the reference is indirect, that is, the one to whom the reference has been made to is not the interviewed. More accurately, when the naming forms are used to mention a third person. The quantitative and qualitative analysis are presented. The data processing methodology was the Variation Theory integrated to the networks analysis of the residents social relations. The results show that in Aparecida do Mundo Novo, the use of morphologically modified names is the most frequent, while in Belo Horizonte the use of names without modifications is the most frequent. After identifying and typifying the interactions between the informants samples, we attribute the results to the networks density degree of each analyzed community. The correlation, the referencing type and the density of the selected networks are also found in Portuguese communities in other periods of time. The diachronic study allowed us to verify that the same process is repeated through the years. This issue study presents more evidence for the acting of the Uniformitarian Principle.